PM10 concentration levels at an urban and background site in Cyprus: the impact of urban sources and dust storms - Achilleos, Souzana; Evans, John S.; Yiallouros, Panayiotis K.; Kleanthous, Savvas; Schwartz, Joel; Koutrakis, Petros (My University, 2014)
Air quality in Cyprus is influenced by both local and transported pollution, including desert dust storms. We examined PM10 concentration data collected in Nicosia (urban representative) from April 1, 1993, through December 11, 2008, and in Ayia Marina (rural background representative) from January 1, 1999, through December 31, 2008. Measurements were conducted using a Tapered Element Oscillating Micro-balance (TEOM). PM10 concentrations, meteorological records, and satellite data were used to identify dust storm days. We investigated long-term trends using a Generalized Additive Model (GAM) after controlling for day of week, month, temperature, wind speed, and relative humidity. In Nicosia, annual PM10 concentrations ranged from 50.4 to 63.8 mg/m3 and exceeded the EU annual standard limit enacted in 2005 of 40 mg/m3 every year. A large, statistically significant impact of urban sources (defined as the difference between urban and background levels) was seen in Nicosia over the period 2000–2008, and was highest during traffic hours, weekdays, cold months, and low wind conditions. Our estimate of the mean (standard error) contribution of urban sources to the daily ambient PM10 was 24.0 (0.4) mg/m3 . The study of yearly trends showed that PM10 levels in Nicosia decreased from 59.4 mg/m3 in 1993 to 49.0 mg/m3 in 2008, probably in part as a result of traffic emission control policies in Cyprus. In Ayia Marina, annual concentrations ranged from 27.3 to 35.6 mg/m3 , and no obvious time trends were observed. The levels measured at the Cyprus background site are comparable to background concentrations reported in other Eastern Mediterranean countries. Average daily PM10 concentrations during desert dust storms were around 100 mg/m3 since 2000 and much higher in earlier years. Despite the large impact of dust storms and their increasing frequency over time, dust storms were responsible for a small fraction of the exceedances of the daily PM10 limit. Implications: This paper examines PM10 concentrations in Nicosia, Cyprus, from 1993 to 2008. The decrease in PM10 levels in Nicosia suggests that the implementation of traffic emission control policies in Cyprus has been effective. However, particle levels still exceeded the European Union annual standard, and dust storms were responsible for a small fraction of the daily PM10 limit exceedances. Other natural particles that are not assessed in this study, such as resuspended soil and sea salt, may be responsible in part for the high particle levels.
Keywords: Air pollutant; Dust; Exhaust gas; Circadian Rhythm; Environmental monitoring; Particulate matter; Vehicle emissions